2022
DOI: 10.3389/fcimb.2022.725342
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Associated Smooth Muscle Tumor and Its Correlation With CD4 Levels in a Patient With HIV Infection

Abstract: Epstein-Barr virus-associated smooth muscle tumor (EBV-SMT) is a rare tumor found in immunocompromised patients, and its treatment is not well-established. A role for antiretroviral therapy in human immunodeficiency virus (HIV)-related EBV-SMT has been proposed; however, the relevance of tumor size, CD4 levels, and immune reconstitution inflammatory syndrome (IRIS) has not been previously reported. We present the first case, to our knowledge, of a tumor that shrank in association with elevated CD4 counts. IRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Our two cases also underwent this treatment strategy and exhibited stable EBV-SMT lesions in follow-up CT scans. Sirolimus, an mTOR signaling pathway inhibitor, not only prevents transplant rejection but also has antineoplastic effect, making it a promising therapeutic drug for EBV-SMT [ 12 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our two cases also underwent this treatment strategy and exhibited stable EBV-SMT lesions in follow-up CT scans. Sirolimus, an mTOR signaling pathway inhibitor, not only prevents transplant rejection but also has antineoplastic effect, making it a promising therapeutic drug for EBV-SMT [ 12 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Deyrup et al examined EBV-SMTs in 19 patients with multiorgan involvement and found that, in each case, the tumors were genetically distinct, suggesting that the multiorgan condition arises from multiple primary tumors rather than metastasis [59]. Moreover, it has been observed that EBV-SMTs related to HIV infection tend to have a higher likelihood of central nervous system involvement [25][26][27]29,31,35,43,45,52,59].…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%
“…The distinctive characteristics of EBV-SMTs comprise the presence of a second population of small, round tumor cells with hyperchromatic, round nuclei and limited amphophilic cytoplasm, as well as an infiltrate of intratumoral lymphocytes [26,[28][29][30]34,36,41,44,45,47,48,50,51,53,55,57]. Other noteworthy features may include increased vascularity resembling hemangiopericytoma (HPC)like vasculature or an appearance reminiscent of an inflammatory pseudotumor (IPT) [27][28][29]34,53]. Visual representations of the key histological features described earlier are also presented in an illustrative case of a lymph node involved with an EBV-SMT (see Figure 2).…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune reconstitution can help T cells to kill tumor cells, thus contributing to tumor shrinkage [ 217 ]. Therefore, although the treatment of EBV-SMT mainly focuses on surgical resection and radiation therapy, immune reconstitution is a potentially promising treatment strategy [ 218 ].…”
Section: Landscape Of Different Ebv-associated Malignanciesmentioning
confidence: 99%